Charismatic, transformational and visionary dimensions in sport leadership : toward news paths for the study of coach-athletes relationships - Gomes, António Rui (2006)
In this paper we suggest possible applications of the charismatic, transformational and visionary leadership approaches to the sports field, to help understand the dynamics of the coach-athlete relationship. We present the results of our research using these concepts to analyze the work of sports managers. We note that few studies have focused on coaches as promoters of charismatic and transformational behaviors on athletes and teams.